Vitamin A inhibits the action of LPS on the intestinal epithelial barrier function and tight junction proteins. Issue 2 (12th February 2019) - He, Caimei; Deng, Jun; Hu, Xin; Zhou, Sichun; Wu, Jingtao; Xiao, Di; Darko, Kwame Oteng; Huang, Yanjun; Tao, Ting; Peng, Mei; Wang, Zhiren; Yang, Xiaoping
Abstract : Inflammation caused by either intrinsic or extrinsic toxins results in intestinal barrier dysfunction, contributing to inflammatory bowel disease (IBD) and other diseases. Abstract : Inflammation caused by either intrinsic or extrinsic toxins results in intestinal barrier dysfunction, contributing to inflammatory bowel disease (IBD) and other diseases. Vitamin A is a widely used food supplement although its mechanistic effect on intestinal structures is largely unknown. The goal of this study was to explore the mechanism by investigating the influence of vitamin A on the intestinal barrier function, represented by tight junctions. IPEC-J2 cells were differentiated on transwell inserts and used as a model of intestinal barrier permeability. Transepithelial electrical resistance (TEER) was used as an indicator of monolayer integrity and paracellular permeability. Western blot and the reverse transcriptase-polymerase chain reaction were used to assess the protein and mRNA expression of tight junction proteins. Immunofluorescence microscopy was used to evaluate the localization and expression of tight junctions. Differentiated cells were treated with a vehicle control (Ctrl), inflammatory stimulus (1 μg mL −1 LPS), LPS co-treatment with 0.1 μmol L −1 Vitamin A (1 μg mL −1 LPS + 0.1 μmol L −1 VA) and 0.1 μmol L −1 Vitamin A. LPS significantly decreased TEER by 24 hours, continuing this effect to 48 hours after application. Vitamin A alleviated the LPS-induced decrease of TEER from 12 hours to 48 hours, while Vitamin A alone enhanced TEER, indicating that Vitamin A attenuated LPS-induced intestinal epithelium permeability. Mechanistically, different concentrations of Vitamin A (0–20 μmol L −1 ) enhanced tight junction protein markers including Zo-1, Occludin and Claudin-1 both at protein and mRNA levels with an optimized dose of 0.1 μmol L −1 . Immunofluorescence results demonstrated that majority of Zo-1 and Claudin-1 is located at the tight junctions, as we expected. LPS reduced the expression of these proteins and Vitamin A reversed LPS-reduced expression of these proteins, consistent with the results of western blot. In conclusion, Vitamin A improves the intestinal barrier function and reverses LPS-induced intestinal barrier damage via enhancing the expression of tight junction proteins.